PENDEKATAN HUMANISTIK DALAM PERKEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Bimas Ritonga; Ahmad Syahri Mubarak; Hasan Basri (Universitas Yudharta Pasuruan, 2023)
This study aims to find out how the Islamic religious education curriculum develops through a humanistic approach and to find out the characteristics of a humanistic Islamic religious education curriculum. The method in this study used the library research method (library study). This method focuses activities on the utilization of library sources to obtain research data. While the technique in collecting data used in this study is content analysis. Content analysis technique is a method used in analyzing a text, both in the form of words, pictures and other forms. The results of this study indicate that the development of an Islamic religious education curriculum through a humanistic approach, namely a legal concept in planning the development of an Islamic religious education curriculum by providing opportunities for students to become more harmonious human beings in carrying out the learning process through several planning, namely: strategic planning, program planning, and planning learning activities.